Endovascular Aneurysm Repair Complicated with Type Ia Endoleak and Presumable Infection Treated with a Fenestrated Endograft - de Niet, Arne; van Schaik, Paul M.; Saleem, Ben R.; Zeebregts, Clark J.; Tielliu, Ignace F. J. (AORTA, 2018)
An 81-year-old patient presented to the emergency room 5 years after infrarenal endovascular aneurysm repair, with a Type Ia endoleak and a presumable infection of the graft material with Listeria monocytogenes. He was treated with a custom-made fenestrated endograft to seal the endoleak and lifelong antibiotic therapy to suppress the infection. Full explantation of graft material is not always preferable, and endovascular treatment combined with antibiotic suppressive therapy is in some cases an appropriate alternative.
Keywords: popliteal aneurysm; aortic aneurysm; Listeria monocytogenes infection; fenestrated endovascular aneurysm repair